Canada’s False Guilty Pleas: Lessons from The Canadian Registry of Wrongful Convictions - Roach, Kent (The Wrongful Conviction Law Review, 2023)
The Canadian Registry of Wrongful Convictions www.wrongfulconviction.ca, like similar registries in the United States and the United Kingdom, was designed to facilitate research on patterns and trends in wrongful convictions. As of its launch in February 2023, 15 of 83 remedied wrongful convictions or 17% were the result of guilty pleas by the accused. Forty percent of the guilty plea wrongful convictions were entered by women. Most of these involved theflawed expert testimony of Charles Smith about the cause of baby deaths. The majority of the 15 remedied guilty plea wrongful convictions were for imagined crimes that did not happen. Almost half (7 of 15) of Canada’s false guilty pleas were taken from racialized people including three Indigenous men, one Black and Indigenous man, another Black man and a Brown man who had recently immigrated from India. Two of the fifteen false guilty pleas were taken from accused persons who had diagnosed with mental health and cognitive challenges. With the exclusion of one false guilty plea to a mandatory murder sentence of life imprisonment and ineligibility for parole for 10 years, the average sentence in the remaining 14 cases was 10 months. This is evidence of “lop-sided” plea deals producing lenient sentences. In two cases, the accused who pled guilty received sentences of time already served in pre-trial custody. A number of strategies to prevent false guilty pleas including abolition of mandatory sentences and better charge and pre-trial detention screening are examined. Nevertheless,it is argued that false guilty pleas are inevitable in high volume criminal justice systems that recognize a guilty plea as a reason to mitigate sentences. This article also raises concerns that both Canada’s appeal courts and its proposed Miscarriage of Justice Review Commission are not well suited to remedying inevitable false guilty pleas.